European green capitals. Best practices for sustainable urban development - Andrea Iacomoni (Agathón)
The contribution, summarizing the results of the research on Green Infrastructures and European Capitals, aims to set a reflection on the quality of cities and on the complex strategies to be pursued, both in terms of intervention scales (structural and process) and areas action (economic, environmental, social), to be implemented continuously over time and in compliance with the specificities of the contexts. With this work, it was intended to highlight how the European Union, in recent decades, has devoted increasing and considerable efforts in prefiguring sustainability objectives, fundamental to address the urban planning policies of individual cities, increasingly oriented to develop strategic plans that pursue a development intelligent and sustainable urban development.